Сказка о рыбаке и рыбке - Пушкин Александр Сергеевич (Серия "Стихи и сказки малышам", 2014)
Экземпляры: ф.16 (20160516) / Инвентарный номер: 47817 / Цена: 74.00 / Сис.шифр: Д / Авт.знак: П 91 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)1